Strategic corporate social responsibility - international student edition. 14 : Sustainable value creation - Chandler, David, 1969- (London : SAGE Publications, 2019)
Why does organizational behavior matter - isn't it just common sense? Organizational Behavior: A Skill-Building Approach helps students answer this question by providing insight into OB concepts and processes through an interactive skill-building approach. Translating the latest research into practical applications, authors Christopher P. Neck, Jeffery D. Houghton, and Emma L. Murray unpack how managers can develop essential skills to unleash the potential of their employees. The text examines how individual characteristics, group dynamics, and organizational factors affect performance, motivation, and job satisfaction, providing students with a holistic understanding of OB. Packed with critical thinking opportunities, experiential exercises, and self-assessments, the new Second Edition provides students with a fun, hands-on introduction to the fascinating world of OB. This title is accompanied by a complete teaching and learning package. Contact your SAGE representative to request a demo. Digital Option / Courseware SAGE Vantage is an intuitive digital platform that delivers this text's content and course materials in a learning experience that offers auto-graded assignments and interactive multimedia tools, all carefully designed to ignite student engagement and drive critical thinking. Built with you and your students in mind, it offers simple course set-up and enables students to better prepare for class. Assignable Video with Assessment Assignable video (available with SAGE Vantage) is tied to learning objectives and curated exclusively for this text to bring concepts to life. LMS Cartridge (formerly known as SAGE Coursepacks): Import this title's instructor resources into your school's learning management system (LMS) and save time. Don't use an LMS? You can still access all of the same online resources for this title via the password-protected Instructor Resource Site. Learn more.
Keywords: elektronické knihy; electronic books; Business & Management -- Business Ethics